Transitional Production of Knowledge For Civic Trust and Social Integration: Social Science in the Transitional Justice Process - Katarzyna Marta Głąb (IKAT: The Indonesian Journal of Southeast Asian Studies, 2019)
This article aims to show that transitional justice should be understood extensively, going beyond the legal-criminal view (transitional justice in the narrow sense). The main argument of research is that social sciences offer a prepared methodological set, without which it is impossible to study these processes effectively, and thus it is impossible to carry out effective social reform, what the cases of some countries show. More andmore often, this is said about the significant role of reconciliation, buildingsocial trust and social cohesion, achieved through extra-legal means, using non-judicial mechanisms. The author intentions to highlight the rooting of transitional justice in this broader sense in social sciences and outline the relationship between truth and political regimes, explaining the dynamic relation of truth-knowledge to political power, but also to highlight the issue of overcoming the problematic universality of transitional justice.